Digital Ethics in the Perspective of Islamic Religious Education: Constructing Religious Awareness in Cyberspace - Parawansah, Hanifah; Hanafi; Kosim; Muttaqien, Moh. Hasan Firghol (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The rapid development of digital technology has created a new space for social interaction that raises significant ethical and moral challenges. Phenomena such as the spread of misinformation, hate speech, and irresponsible online behavior indicate a lack of ethical awareness in digital media use. This article aims to examine digital ethics from the perspective of Islamic Religious Education as an effort to build religious awareness in cyberspace. This study employs a qualitative approach through library research by analyzing primary and secondary sources, including the Qur’an, hadith, literature on Islamic Religious Education, Islamic ethics, and contemporary studies on digital ethics. Data were analyzed using descriptive-interpretative content analysis. The findings reveal that digital ethics in the perspective of Islamic Religious Education is grounded in religious values such as trustworthiness, honesty, proper conduct, responsibility, and awareness of divine supervision. These values play a crucial role in shaping ethical and moral digital behavior. Islamic Religious Education contributes strategically to fostering religious awareness in the digital sphere by internalizing faith-based values that encourage self-control and moral responsibility in digital activities. This study highlights the relevance of integrating digital ethics within Islamic Religious Education as a normative and educational approach to addressing moral challenges in the digital era.